The impact of the Albigensian Crusade on the Kingdom of Aragon - oudjdi, khalfallah (The Algerian Historical Journal, 2026)
Through this study, we will try to identify the Crusade that the papacy declared against the many heretics in southern France, and how this movement affected the political, religious, social and economic conditions of that region. The Kingdom of Aragon was the most affected by this movement, when it lost one of its most famous and bravest kings, Pedro II (the Chaste), who found himself involved in this war against his will, just as the Kingdom of Aragon lost its most famous follower in this war in southern France .